IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA BANK PEMBIAYAAN RAKYAT SYARIAH IKHSANUL AMAL KECAMATAN GOMBONG KABUPATEN KEBUMEN - Hajar Hajar Mukaromah (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study was to determine the implementation of Good Corporate Governance at PT BPRS Ikhsanul Amal Kebumen. Good Corporate Governance is a healthy corporate principle that needs to be implemented in the management of the company which is carried out to protect the interests of the company in order to achieve the company's goals and objectives. PT. BPRS Ikhsanul Amal in implementing good corporate governance is guided by 6 principles, namely: openness, accountability, responsibility, professionalism, fairness and compliance with sharia principles. This type of research is qualitative research and library research using a descriptive approach. In this study the authors describe how the implementation of good corporate governance at the Islamic People's Financing Bank Ikhsanul Amal. Methods of data collection using interviews, observation and documentation. Based on the results of this study, it can be concluded that the implementation of good corporate governance at the Islamic People's Financing Bank Ikhsanul Amal has been carried out properly based on bank and company regulations.